Assessing automobile attributes influencing customer's satisfaction towards national car consumption among race groups / Nur Hazwani Zolkifly … [et al.] - Zolkifly, Nur Hazwani (Research Management Institute (RMI), 2011)
Rapid globalization of market leaves impact to Malaysian automobile industry as a whole. Despite of high sales, customer's satisfactions towards national car were low as compared to imported cars. This prompted the current investigation with the objectives to identify the most important automobile attributes influencing customer's satisfaction and also to determine the most appealing automobile attributes among major ethnic groups in Malaysia. This study employs survey approach where 370 responses were collected from car owners and drivers of 1.3cc engine size in Klang Valley area. Results from the regression analysis showed the resale value were the major factors which influenced customer satisfaction, followed by vehicle appearance and safety attributes. Secondly, all major ethnic groups; Malay, Indian and Chinese were influenced mostly by safety feature. In addition, the result depict that Chinese has lower satisfaction level towards national car consumption as compared to other races.